Bibliometric Insights into the Indian Journal of Finance : Mapping Intellectual Contributions - Singh, Raj Kumar; Saxena, Charu; Aggarwal, Shalini; Prerna; Singh, Yashvardhan (Indian Journal of Finance, 2025)
Purpose : This study aimed to conduct a bibliometric analysis of the Indian Journal of Finance to uncover key contributions and highlight emerging research trends in finance. Methodology : Utilizing the SPAR-4-SLR protocol, 739 documents published in the journal between 2010 and 2024 were selected from the Scopus database and examined using VOS-viewer and R-studio software. Findings : The analysis highlighted publication trends, citation patterns, influential authors, and countries, along with the thematic evolution of research. The peak publication was recorded in 2010, while 2018 marked the most impactful year. The most cited paper received 35 citations, with Kumar, S., and Tripathi as prominent contributors. The thematic developments were mapped across three distinct periods. Practical Implications : The insights gained offered a foundation for future research in finance by identifying unexplored areas and methodological best practices for conducting rigorous research. Originality/Value : The study contributed significantly to academic and professional communities by mapping out a comprehensive framework of key theories, variables, constructs, and methodological strategies used in the field.